Antimicrobial Activity of Chewing Sticks of Jimma – Ethiopia against - Thiyagarajan, Kothai Seshathri and Thirunalasundari (Journal of Phytology, 2011)
Chewing sticks were used to maintain oral hygiene / infection in the study area Jimma. Its use is a re-emerging science because of wide range of antibiotic resistant microbes and adverse effect of the dentifrices. Hence the objective of the study was to identify an oral health problem, common in the study area, the probable organism responsible for the disease and to screen the medicinal plants identified against the pathogen. Ethanobotanical survey was used as a tool to identify the oral problem and the medicinal plants. The causative organism was identified as Streptococcus pyogenes by throat swab culture. The medicinal plants reported in the survey to manage oral hygiene / infection were screened for their antimicrobial activity (Perez et al., 1991) against the isolated pathogen. Among the tested plants, Juniperus procera which was not documented as a chewing stick and tested against S.pyogenes before, showed maximum activity. The current research validates the use of Juniperus procera as chewing stick.